1990
DOI: 10.1007/bf01316682
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of gangliosides in the interaction between BK virus and Vero cells

Abstract: BK virus infectivity was inhibited by gangliosides extracted from Vero cells and by standard preparations of different gangliosides. Gangliosides were also able to restore the susceptibility of glycosidase-treated Vero cells to BK virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 18 publications
1
44
0
3
Order By: Relevance
“…Early receptor studies elucidated a role for sialic acids and polysialylated gangliosides in BKV infectious entry into Vero cells and in virus binding to red blood cells (35,40,41). The linkage of sialic acid and the potential role of glycoproteins in infection were not elucidated in these early studies.…”
mentioning
confidence: 99%
“…Early receptor studies elucidated a role for sialic acids and polysialylated gangliosides in BKV infectious entry into Vero cells and in virus binding to red blood cells (35,40,41). The linkage of sialic acid and the potential role of glycoproteins in infection were not elucidated in these early studies.…”
mentioning
confidence: 99%
“…Other studies have also shown that the addition of soluble gangliosides attenuates BKV-mediated hemagglutination (45). Treatment of Vero cells with neuraminidase, which cleaves sialic acid residues in the sugar moiety contained in many gangliosides and glycoproteins, inhibits BKV infection, and the addition of a mixture of Vero cell gangliosides to these treated cells restores infection (44). Gangliosides have been identified as receptors for the polyomaviruses SV40 and Py, both of which also enter the cell via a caveola-dependent mechanism (19,49).…”
mentioning
confidence: 99%
“…Though the exact identity of the BK receptor(s) is unknown, evidence suggests that gangliosides type II, GD1a, and GT play important roles in the initial interaction between BKV and the permissive monkey kidney (Vero) cell line, as well as in BKV hemagglutination of human type O red blood cells (54,59,60). Following penetration of the target cell membrane and BKV internalization, the viral genome is delivered to the host cell nucleus.…”
mentioning
confidence: 99%